Effects of sintering condition on phase formation, microstructure and dielectric properties of lead titanate ceramics - R. Wongmaneerung (2018)
Lead titanate ceramics have been prepared by two different processing methods: conventional (or single-stage) and two-stage sintering. Effects of designed sintering conditions on phase formation, densification, microstructure and dielectric properties of the ceramics were characterized via X-ray diffraction, Archimedes density measurement, scanning electron microscopy and dielectric measurement, respectively. The potentiality of a two-stage sintering technique as a simple ceramic fabrication method to obtain highly dense and pure lead titanate ceramics was demonstrated. It has been found that, under suitable two-stage sintering conditions, dense perovskite lead titanate ceramics can be successfully achieved with better dielectric properties than those of ceramics from a single-stage sintering technique. © Springer-Verlag 2007.